Examination of enterpreneurship ecosystem in Debrecen from the direction of open innovation spaces - Horváth , Adrienn (Applied Studies in Agribusiness and Commerce, 2014)
Innovation is not just a technology, but it is rather a comprehensive vision of what the future should look like and which requires changes in many ambits. Innovation is driven by people’s needs, ambitions and dreams, and it is necessary that people at different positions in the society change the way they work and live. Innovation, as a result of human interactions, often fails because people do not understand each other, as they belong to different worlds which have their own languages and cultures. While innovation system-like thinking recognizes that the needs are a good mix of factors for innovation, it is hard to establish the perfect mix beforehand: innovation systems and policies need to be adaptive” (Klerkx, Mierlo & Leeuwis 2012). I tried to bring this complex vision to our future. The actuality of the topic is provided by the fact that we are in the period of the development of digital industrial revolution, on the peak of the technology innovations, slowly resulting in the revolutions of the machines. These technological innovations, trends, equipment or new technological achievements often make our work easier, or they may replace us, and will bring changes transforming the world with them. At present era, the availability and use of the relevant knowledge is essential. In Western Europe and in other more developed countries different spaces provide places for evolving various trends, applying the acquired knowledge, e.g. development of Silicon Valley, polices, clusters, co-workings. These innovative spaces may form a bridge for evolving a global, international or regional technology and knowledge transfer, sharing our knowledge and developing our competitiveness. They may be the engine of a “new world”. The entrepreneurship ecosystem in Debrecen was investigated regarding the presence of open innovation spaces. Though Debrecen has already had open innovation spaces, it does not have space operating as HUB. „HUB is a global platform, where people from all corners of the planet connect and engage in collaborative action to realize enterprising ideas for a better world” (HUB GMBH 2012). Furthermore, I studied the fact that why the creation of HUB in Debrecen is reasonable concerning every sector, and what characteristics this space may have. In order to analyze my hypotheses, I used questionnaires made by Delphi survey. During the process experts of this field were asked in two turns. Selecting the experts occurred on the basis of Helix model.